Machine learning methods for better water quality prediction - Najah Ahmed A.; Binti Othman F.; Abdulmohsin Afan H.; Khaleel Ibrahim R.; Ming Fai C.; Shabbir Hossain M.; Ehteram M.; Elshafie A. (Elsevier B.V., 2023)
Forecasting; Fuzzy neural networks; Fuzzy systems; Large dataset; Learning systems; Machine learning; Multilayer neural networks; Network layers; Quality control; Radial basis function networks; Random errors; Systematic errors; Water management; Water quality; Adaptive neuro-fuzzy inference system; Multi-layer perceptron neural networks; Neuro-fuzzy inference systems; Radial basis function neural networks; Water quality parameters; Water quality predictions; Wavelet de-noising techniques; WDT-ANFIS; Fuzzy inference; accuracy assessment; complexity; data set; environmental degradation; error analysis; experimental study; human activity; machine learning; nonlinearity; parameterization; prediction; water quality; Johor; Johor Basin; Malaysia; West Malaysia